ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI MINAT KONSUMEN UNTUK MENGGUNAKAN E-COMMERCE PADA APLIKASI TOKOPEDIA DENGAN MENGGUNAKAN UTAUT 2 - Maheswari, Galuh Dahayu; Meiranto, Wahyu (Diponegoro Journal of Accounting, 2024)
E-commerce is an example of a form of finance technology that requires a smartphone and internet network. However, the security factor is one of the barriers to the use of e-commerce. The purpose of this study is to examine the factors that influence the interest in acceptance and use of e-commerce on the Tokopedia application in Semarang City.The research was conducted using the Unified Theory of Acceptance and Use of Technology 2 (UTAUT 2) model consisting of performance expectancy, effort expectancy, facilitating conditions, hedonic motivation, behavioral intention and use behavior with the addition of perceived security and perceived trust variables. This research was tested using PLS-SEM analysis with the SmartPLS 3 application on 100 samples who were Tokopedia application users in Semarang City.            The results showed that effort expectancy, hedonic motivation, and perceived trust were proven to have a positive and significant effect on behavioral intention to use Tokopedia. Meanwhile, performance expectancy, facilitating conditions, and perceived security have no effect on behavioral intention. The test results also show that behavioral intentions are proven to have a positive and significant effect on the use behavior of Tokopedia. Furthermore, behavioral intention is known to be the most significant determining factor.